A comparison between the use of popular phrases in english and spanish - Trebucq, María Dolores (2010)
Native speakers interpret and transmit their ideas, beliefs and thoughts with amazing accuracy and economy of words by resorting to idioms or popular phrases. This paper focuses on a number of idiomatic expressions in English and Spanish and traces their origins and uses. It aims to show that the lexical items through which meaning is conveyed may be the same in English and Spanish or may vary from one culture to the other, depending on the way in which certain events are perceived by the community members. It also shows that some idioms or popular phrases may be so closely tied to the socio-cultural history of each speech community that they do not have equivalent meaning associations in the language contrasted. In conclusion, the work demonstrates that the meanings conveyed by idiomatic expressions, at least in English and Spanish, are closely connected with the experiences undergone by the speech communities in which they are conventionally used.